Blastomycosis Presenting as Multiple Splenic Masses - Tahir Ijaz; Samy El-Sayed; Garry Schroeder; Robert O’Connor; Julio Pintin-Quezada; Howard Greenberg (Canadian Journal of Infectious Diseases)
Blastomyces dermatitidis is a fungus that causes a wide spectrum of disease in humans. The clinical and pathological entity of splenic abscess due to blastomycosis is extremely rare. A case of splenic blastomycosis is reported, and its cytopathological and radiological features are described.